P-hydroxybenzaldehyde modified macroporous chloromethylated polystyrene as well as preparation method and application thereof
By modifying macroporous chloromethylated polystyrene with oxygen-containing aromatic functional compounds, the problem of insufficient adsorption capacity of CMPs was solved, and a super-cross-linked resin with high efficiency in adsorbing aniline was prepared, achieving high efficiency adsorption and renewability.
Patent Information
- Application Number
- CN202510995708.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-18
- Publication Date
- 2025-10-28
AI Technical Summary
Existing macroporous chloromethylated polystyrene (CMPs) have limited adsorption capacity, low selectivity, and poor regeneration performance when adsorbing aromatic organic compounds. Existing chemical modification methods are costly or ineffective.
By introducing the oxygen-containing aromatic functional compound p-hydroxybenzaldehyde to undergo nucleophilic substitution reaction on CMPs, followed by Friedel-Crafts alkylation reaction, the hyper-crosslinked resin PHBA-HCPs was prepared to improve its adsorption performance for aniline in aqueous solution.
The adsorption performance of the polymer for aniline in aqueous solution was significantly improved, its specific surface area and adsorption capacity of heteroatom aromatic functional groups were enhanced, and efficient aniline adsorption and reusability were achieved.
Smart Images

Figure CN120842462A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of adsorbent technology, specifically to a p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene, its preparation method, and its application. Background Technology
[0002] Aniline is a common and important basic chemical raw material, widely used in dyes, pesticides, rubber, petrochemicals, pharmaceuticals, and other industries. The widespread industrial use of this compound inevitably generates large amounts of aniline-contaminated wastewater, causing environmental pollution. Therefore, the treatment of aniline-containing wastewater is particularly important. Among various remediation methods, adsorption-based separation methods have become the preferred strategy for aniline removal due to their simplicity, cost-effectiveness, high efficiency, and the reusability of the adsorbent. Macroporous chloromethyl polystyrene (CMPs) are often used as adsorbent materials due to their high surface area, good chemical stability, and mechanical strength. However, CMPs suffer from limited adsorption capacity, low selectivity, and poor regeneration performance when adsorbing aromatic organic compounds. These inherent defects have prompted research to shift towards chemical modification to enhance their adsorption performance.
[0003] The most common method for chemically modifying CMPs is to introduce functional groups or heteroatoms through post-crosslinking reactions or Friedel-Crafts alkylation reactions to enhance their adsorption performance for targeted molecules. Existing preparation methods are either overly complex and costly, or the resulting adsorbents have limited adsorption capacity for organic matter, thus restricting their applications. Summary of the Invention
[0004] The purpose of this invention is to provide a p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene (CMPs), its preparation method, and its applications. By introducing the oxygen-containing aromatic functional compound PHBA to modify CMPs, a nucleophilic substitution reaction is first carried out, followed by a Friedel-Crafts alkylation reaction to prepare the hypercrosslinked resin PHBA-HCPs. The excellent specific surface area and the introduction of aromatic functional groups containing heteroatoms (especially oxygen-rich groups) greatly improve the adsorption performance of this polymer for aniline in aqueous solutions.
[0005] The technical solution of this invention is implemented as follows:
[0006] This invention provides a method for preparing p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene, comprising the following steps:
[0007] S1. Macroporous chloromethylated polystyrene (CMPs) were swollen in N,N-dimethylformamide, and then p-hydroxybenzaldehyde (PHBA) and potassium carbonate were added to the reaction mixture. The mixture was heated and stirred. After the reaction was completed, the mixture was washed and dried to obtain PHBA-CMPs.
[0008] S2. PHBA-CMPs were swollen in 1,2-dichloroethane. Dimethoxymethane and the catalyst were added to the reaction system. After low-temperature pre-crosslinking, the mixture was heated and stirred. After the reaction was completed, the mixture was washed and dried to obtain p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene PHBA-HCPs.
[0009] As a further improvement of the present invention, the mass ratio of macroporous chloromethylated polystyrene (CMPs), p-hydroxybenzaldehyde (PHBA), and potassium carbonate is 35-45:20-25:10-15.
[0010] As a further improvement of the present invention, the heating and stirring reaction in step S1 is carried out at a temperature of 95-105°C for a time of 18-22 hours.
[0011] As a further improvement of the present invention, the catalyst is selected from at least one of ferric chloride, aluminum chloride, and bismuth trichloride.
[0012] As a further improvement of the present invention, when the catalyst is ferric chloride, the mixture is heated to 15-25°C for pre-crosslinking for 3-5 hours, and then heated to 95-105°C for stirring reaction for 3-5 hours. The mass ratio of PHBA-CMPs, dimethoxymethane, and ferric chloride is 20:25-35:23-27.
[0013] As a further improvement of the present invention, when the catalyst is aluminum trichloride, the reaction is carried out by heating to 15-25°C for pre-crosslinking for 3-5 hours, then heating to 55-65°C and stirring for 3-5 hours, then heating and stirring at 75-85°C for 10-15 hours, and finally heating and stirring at 95-105°C for 20-28 hours. The mass ratio of PHBA-CMPs, dimethoxymethane, and aluminum trichloride is 20:25-35:22-25.
[0014] As a further improvement of the present invention, when the catalyst is bismuth trichloride, the reaction is carried out by heating to 15-25°C for pre-crosslinking for 3-5 hours, then heating to 35-45°C and stirring for 3-5 hours, then heating and stirring at 75-85°C for 10-15 hours, and finally heating and stirring at 95-105°C for 20-28 hours. The mass ratio of PHBA-CMPs, dimethoxymethane, and bismuth trichloride is 20:25-35:5-10.
[0015] The present invention further protects a p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene prepared by the above-described preparation method.
[0016] This invention further protects the application of the above-mentioned p-hydroxybenzaldehyde modified macroporous chloromethylated polystyrene in adsorbing organic matter in solution.
[0017] As a further improvement of the present invention, the organic compound is aniline.
[0018] The present invention has the following beneficial effects: The present invention introduces the oxygen-containing aromatic functional compound PHBA to modify CMPs, firstly through a nucleophilic substitution reaction, and then through a Friedel-Crafts alkylation reaction to prepare a hypercrosslinked resin. The excellent specific surface area and the introduction of aromatic functional groups containing heteroatoms (especially oxygen-rich groups) greatly improve the adsorption performance of this polymer for aniline in aqueous solutions. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 Fourier transform infrared spectra of p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene prepared in Examples 1-3;
[0021] Figure 2 The images show the (A) N2 adsorption-desorption isotherms and (B) pore size distribution of the p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene prepared in Examples 1-3.
[0022] Figure 3 SEM images of p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene prepared in Examples 1-3;
[0023] Figure 4 TEM images of p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene prepared in Examples 1-3;
[0024] Figure 5 XPS images of p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene prepared in Examples 1-3;
[0025] Figure 6 The TGA curves of p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene obtained in Examples 1-3 are shown.
[0026] Figure 7 The following are the equilibrium adsorption isotherms of aniline at 288 K for p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene prepared in Examples 1-3, and the equilibrium adsorption isotherms of PHBA-HCPs-Al at different temperatures.
[0027] Figure 8The kinetic adsorption diagrams of aniline by PHBA-HCPs-Al at 288, 298 and 308 K are shown.
[0028] Figure 9 The graph shows the effect of resin dosage on aniline removal rate.
[0029] Figure 10 Figure for the reuse and stability of PHBA-HCPs-Al. Detailed Implementation
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] Example 1
[0032] This embodiment provides a method for preparing p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene, including the following steps:
[0033] S1. 40.8 g of macroporous chloromethylated polystyrene (CMPs) was swollen in 120 mL of N,N-dimethylformamide for 24 h. Then, 23.3 g of p-hydroxybenzaldehyde (PHBA) and 12.0 g of potassium carbonate were added to the reaction mixture. The mixture was heated to 100 °C and stirred for 20 h. After the reaction was completed, the product was washed with 1% (v / v) hydrochloric acid-ethanol solution to remove residues, followed by Soxhlet extraction and washing with anhydrous ethanol for 48 h. Finally, the product was dried under vacuum at 80 °C for 12 h to obtain PHBA-CMPs.
[0034] S2. 20g of PHBA-CMPs was swollen in 160mL of 1,2-dichloroethane for 24h. 30g of dimethoxymethane and 26.7g of ferric chloride were added to the reaction system. After pre-crosslinking at 20℃ for 4h, the temperature was raised to 100℃ and stirred for 4h. After the reaction was completed, the post-treatment was the same as in step S1 to obtain p-hydroxybenzaldehyde modified macroporous chloromethylated polystyrene 1, denoted as PHBA-HCPs-Fe.
[0035] Example 2
[0036] This embodiment provides a method for preparing p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene, including the following steps:
[0037] S1. 40.8 g of macroporous chloromethylated polystyrene CMPs were swollen in 120 mL of N,N-dimethylformamide for 24 h. Then, 23.3 g of p-hydroxybenzaldehyde PHBA and 12.0 g of potassium carbonate were added to the reaction mixture. The mixture was heated to 100 °C and stirred for 20 h. After the reaction was completed, the post-treatment was the same as step S1 in Example 1 to obtain PHBA-CMPs.
[0038] S2. 20g of PHBA-CMPs was initially expanded in 160mL of 1,2-dichloroethane for 24h. 30g of dimethoxymethane and 22.5g of aluminum chloride were added to the reaction system. After pre-crosslinking at 20℃ for 4h, the temperature was raised to 60℃ and stirred for 4h. Then, the reaction was stirred at 80℃ for 12h and at 100℃ for 24h. After the reaction was completed, the post-treatment was the same as step S1 in Example 1 to obtain p-hydroxybenzaldehyde modified macroporous chloromethylated polystyrene 2, denoted as PHBA-HCPs-Al.
[0039] Example 3
[0040] This embodiment provides a method for preparing p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene, including the following steps:
[0041] S1. 40.8 g of macroporous chloromethylated polystyrene CMPs were swollen in 120 mL of N,N-dimethylformamide for 24 h. Then, 23.3 g of p-hydroxybenzaldehyde PHBA and 12.0 g of potassium carbonate were added to the reaction mixture. The mixture was heated to 100 °C and stirred for 20 h. After the reaction was completed, the post-treatment was the same as step S1 in Example 1 to obtain PHBA-CMPs.
[0042] S2. 20g of PHBA-CMPs was initially expanded in 160mL of 1,2-dichloroethane for 24h. 30g of dimethoxymethane and 6.7g of bismuth trichloride were added to the reaction system. After pre-crosslinking at 20℃ for 4h, the temperature was raised to 40℃ and stirred for 4h. Then, the reaction was stirred at 80℃ for 12h and at 100℃ for 24h. After the reaction was completed, the post-treatment was the same as step S1 in Example 1 to obtain p-hydroxybenzaldehyde modified macroporous chloromethylated polystyrene 3, denoted as PHBA-HCPs-Bi.
[0043] Test Example 1
[0044] FT-IR such as Figure 1 As shown. 3450cm -1 A series of wavelengths in the vicinity correspond to the stretching vibrations of the hydroxyl group. 3000~2800cm -1 The vibration peak at 1700 cm⁻¹ is attributed to the tensile vibration of -CH₂. -1The presence of an aldehyde group was confirmed by a distinct carbonyl vibration peak at 1260 cm⁻¹. -1 The contrast between the nucleophilic substitution and the weakened C-Cl stretching vibration following Friedel-Crafts alkylation is striking. No distinct amine peak was observed after adsorption because the characteristic peaks of aniline and hydroxyl groups overlap.
[0045] Nitrogen physical adsorption analysis ( Figure 2 The results show that the isotherms of the three samples are type II, and the hysteresis loops are type H3, exhibiting characteristics of a mesoporous structure. Structural parameters are shown in Table 1. The S... BET 、V total The average pore size is equal to that of the two, while PHBA-HCPs-Bi is not the same, and its structural parameters are not ideal, resulting in poor adsorption capacity.
[0046] Table 1 Structural parameters of the resin
[0047] <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Micropore specific surface area (m 2 / g)]]> <![CDATA[Total pore volume (cm 3 / g)]]> <![CDATA[Micropore pore volume (cm 3 / g)]]> Average pore size (nm) PHBA-HCPs-Al 326.2 272.4 0.5266 0.1442 6.4565 PHBA-HCPs-Fe 310.4 265.6 0.4901 0.1426 6.3154 PHBA-HCPs-Bi 181.1 136.4 0.5207 0.0733 11.4992
[0048] Figure 3 SEM images of four samples are presented. PHBA-HCPs-Al exhibits both small particles and aggregated blocky structures, indicating that AlCl3 catalysis induces surface diversification, consistent with BET surface area measurements. In contrast, the other three samples show a blocky surface structure, and this surface morphology diversification also benefits aniline adsorption. After use, PHBA-HCPs-Al shows slight aggregation, while the morphology of PHBA-HCPs-Fe and PHBA-HCPs-Bi changes significantly, with a marked increase in small particles during aniline adsorption.
[0049] Figure 4 TEM images of PHBA-HCPs-Al (A), PHBA-HCPs-Fe (B), PHBA-HCPs-Bi (C), and PHBA-CMPs (D) are shown. A porous structure characterized by alternating dark and bright areas is observed, indicating the presence of numerous pore channels, consistent with the results of SEM and BET tests.
[0050] Figure 5 (A) shows the binding energy of C1s (284.8 eV) and O1s (~532.8 eV). Three chemical states were found in the C1s spectrum: ~284.8 eV (CC), ~286.5 eV (CO), and ~288.5 eV (π-π transition). Figure 5 (B)). Meanwhile, from Figure 5(C) It can be seen that the O1s spectrum can be fitted to three peaks at ~532.0, ~533.4, and ~535.1 eV, which are attributed to CO, C=O, and physically adsorbed water, respectively. This confirms the presence of oxygen functional groups introduced through PHBA crosslinking.
[0051] Figure 6 The TGA profiles of four samples are shown. Significant mass loss was observed in the samples within the temperature range of 300–700 °C. Mass loss increased once the temperature exceeded 300 °C due to the cracking of the resin skeleton caused by thermal decomposition. Importantly, the actual adsorption process occurred at temperatures well below 200 °C, ensuring that the practical utility of the adsorbent samples remained unimpaired. Notably, there was no substantial difference in the final mass loss of the three adsorbents prepared with different catalysts and crosslinking agents. This result is consistent with our expectations; minor differences may be a consequence of the testing process. The higher weight loss rate of PHBA-CMPs compared to CMPs strongly suggests that PHBA was successfully incorporated into CMPs via nucleophilic substitution, and the introduction of the functional monomer PHBA reduced its thermal stability.
[0052] First, CMPs and PHBA-CMPs were directly used as adsorbents to adsorb aniline, but the adsorption efficiency was found to be very low, making it impossible to perform either type of fitting. The equilibrium adsorption isotherms of aniline with the three adsorbents were investigated at 288, 298, and 308 K (see [link to study]). Figure 7 ).like Figure 7 As shown in (A), the results indicate that all resins have high adsorption efficiency for aniline. Figure 7 (B) shows that all resins exhibited relatively high equilibrium adsorption capacities. When Ce was set at 100 mg / L, the order of qe was: PHBA-HCPs-Al (94.9 mg / g) > PHBA-HCPs-Fe (69.7 mg / g) > PHBA-HCPs-Bi (45.9 mg / g). Compared to PHBA-HCPs-Fe and PHBA-HCPs-Bi, PHBA-HCPs-Al showed a higher aniline adsorption capacity. Besides hydrophobic interactions, π-π stacking, van der Waals forces, and acid-base interactions, its larger specific surface area (S) also contributed to this. BET ) and total pore volume (V total The abundance of micropores / mesopores also significantly enhances this adsorption performance.
[0053] The balanced data were fitted using the Langmuir and Freundlich model, such as Figure 7 As shown in (A). The Freundlich model was determined to be more suitable for describing the experimental data, with a correlation coefficient (R²) exceeding 0.99. The maximum adsorption capacities (q) of PHBA-HCPs-Al, -Fe, and -Bi at 288 K were... maxThe values were calculated to be 221.9, 142.9, and 108.7 mg / g, respectively. The adsorption isotherms of PHBA-HCPs-Al at different temperatures (288, 298, and 308 K) are shown below. Figure 7 As shown in (B), the adsorption capacity of aniline increases as the temperature decreases, indicating that this is an exothermic process.
[0054] Thermodynamic analysis of the aniline adsorption system was conducted using the Freundlich model of PHBA-HCPs-Al at different temperatures, focusing on the changes in parameters (such as ΔH, ΔS, and ΔG). The parameter calculation formulas are as follows:
[0055] (1)
[0056] (2)
[0057] Here, R = 8.314 J / (mol·K). The values of ΔH, ΔS, and ΔG can be determined by equations (3) and (4). The negative value of ΔH (-19.14 kJ / mol) indicates that it is an exothermic adsorption mechanism. For ΔG, the values at 288, 298, and 308 K are 0.53, 1.21, and 1.89 kJ / mol, respectively, indicating that increasing temperature is beneficial to the adsorption of aniline.
[0058] Figure 8 The adsorption kinetics of aniline for three samples at different temperatures are shown. Equilibrium data were analyzed using pseudo-first-order and pseudo-second-order models. The pseudo-second-order model provided a better fit to the equilibrium data, with R0... 2 The adsorption rate exceeds 0.98. PHBA-HCPs-Al possesses abundant microporous and mesoporous structures. This structural feature allows aniline molecules to diffuse rapidly, thus significantly reducing the equilibrium time. Interestingly, although higher ambient temperatures generally enhance the diffusion of aniline molecules, the adsorption process is exothermic. Conversely, the adsorption rate is faster at lower temperatures. For example, at 288 K, equilibrium is reached within 180 minutes.
[0059] Using three polymers as adsorbents, the pH of the solution was adjusted from 3.6 to 13.3 by adding HCl / NaOH, and the effect of pH on the adsorbents was investigated. Within the pH range of 5.3 to 7.0, the adsorption capacity of all three adsorbents initially increased and then decreased with increasing pH. The adsorbents exhibited good adsorption performance under acidic conditions. Therefore, the adsorption rate reached its maximum at an initial solution pH of 5.3.
[0060] Figure 9The relationship between resin dosage and aniline removal rate was demonstrated. Resin dosages ranging from 1.0 g to 19.0 g were evaluated with an initial aniline concentration of 501.7 mg / L. Adding 19.0 g of PHBA-HCPs-Al to 50 mL of aniline solution resulted in an adsorption efficiency of 87.0%, confirming its excellent adsorption performance. The experimental results indicate that PHBA-HCPs-Al has a significant effect on aniline removal.
[0061] After adsorption, the used PHBA-HCPs-Al was washed sequentially with ethanol, dilute hydrochloric acid, and dilute NaOH solution, followed by Soxhlet extraction and dynamic desorption using 0.1 mol / L HCl (w / v) and 60% ethanol (v / v) as desorption solvents for 5 h. After desorption, the resin was filtered and washed alternately with ethanol and deionized water. It was then vacuum dried to maintain its reusability. After 5 cycles, the aniline adsorption was approximately equal to the initial adsorption, indicating significant reusability and regenerability. Figure 10 ).
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene, characterized in that, Includes the following steps: S1. Macroporous chloromethylated polystyrene (CMPs) were swollen in N,N-dimethylformamide, and then p-hydroxybenzaldehyde (PHBA) and potassium carbonate were added to the reaction mixture. The mixture was heated and stirred. After the reaction was completed, the mixture was washed and dried to obtain PHBA-CMPs. S2. PHBA-CMPs were initially expanded in 1,2-dichloroethane. Dimethoxymethane and the catalyst were added to the reaction system. After pre-crosslinking, the mixture was heated and stirred. After the reaction was completed, the mixture was washed and dried to obtain p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene PHBA-HCPs.
2. The preparation method according to claim 1, characterized in that, The mass ratio of macroporous chloromethylated polystyrene (CMPs), p-hydroxybenzaldehyde (PHBA), and potassium carbonate is 35-45:20-25:10-15.
3. The preparation method according to claim 1, characterized in that, The heating and stirring reaction in step S1 is carried out at a temperature of 95-105℃ for 18-22 hours.
4. The preparation method according to claim 1, characterized in that, The catalyst is selected from at least one of ferric chloride, aluminum chloride, and bismuth trichloride.
5. The preparation method according to claim 4, characterized in that, When the catalyst is ferric chloride, the mixture is heated to 15-25°C for pre-crosslinking for 3-5 hours, then heated to 95-105°C and stirred for 3-5 hours. The mass ratio of PHBA-CMPs, dimethoxymethane, and ferric chloride is 20:25-35:23-27.
6. The preparation method according to claim 4, characterized in that, When the catalyst is aluminum trichloride, the mixture is heated to 15-25°C for pre-crosslinking for 3-5 hours, then heated to 55-65°C and stirred for 3-5 hours, then heated and stirred at 75-85°C for 10-15 hours, and finally heated and stirred at 95-105°C for 20-28 hours. The mass ratio of PHBA-CMPs, dimethoxymethane, and aluminum trichloride is 20:25-35:22-25.
7. The preparation method according to claim 4, characterized in that, When the catalyst is bismuth trichloride, the mixture is heated to 15-25°C for pre-crosslinking for 3-5 hours, then heated to 35-45°C and stirred for 3-5 hours, then heated and stirred at 75-85°C for 10-15 hours, and finally heated and stirred at 95-105°C for 20-28 hours. The mass ratio of PHBA-CMPs, dimethoxymethane, and bismuth trichloride is 20:25-35:5-10.
8. A p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene prepared by the preparation method according to any one of claims 1-7.
9. The application of p-hydroxybenzaldehyde-modified macroporous chloromethylated polystyrene as described in claim 8 in the adsorption of organic matter in solution.
10. The application according to claim 9, characterized in that, The organic compound is aniline.